Foote Mineral Company lithium brine evaporation panels - Foote Mineral Company (1969)
General view of the Foote Mineral Company's lithium brine evaporation panels located in Silver Peak, Nevada. A bulk supplier of industrial minerals, the Foote Mineral Company began extracting lithium from below Silver Peak's Clayton Valley in 1966. The Vanadium Corporation of America merged into the Foote Mineral Company in 1967.
Keywords: Foote Mineral Company; Vanadium Corporation of America; Nevada--Silver Peak; Steel alloy industry; Lithium; Vanadium; Mineral industries; Mines and mineral resources